Policy and research in education. Sources, actors and soupcons - Pacheco Méndez, Teresa (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Education has been one of the social processes on which much attention has been given in the design and implementation of public policies, and by the university social research. Even though the political task and the scientist field take care of own regulations of their corresponding traditions, their respective actors appeal, in the case of education, the design and use of certain conceptual and instrumental resources that largely condition the reach and social and scientific impact of their results. This paper identifies and discusses the main conceptual and technical- instrumental obstacles facing policy makers and researchers, in the specific case of education, proposing some guidelines that ensure the significance of their actions.